Studi Komparasi Pemanfaatan Bahan Pemantap Tanah Jenis Lateks dan Polyacrilamide (Pam) dalam Campuran Hydroseeding terhadap Pertumbuhan Vegetasi Jenis Rumput dan Cover Crop - Sri Yeni Mulyani (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2018)
Hydroseeding is an alternative to traditional seed-sowing vegetative technology by mixing other ingredients such as tackifiers (soil amendment), fertilizers, mulch, water, or other materials sprayed using hydraulic pumps (Siswomartono, 1989). In general, the soil amendment used in the hydroseeding mixture is a type of polyacrilamide (PAM). The use of PAM in hydroseeding mixtures still has a deficiency of less stable soil aggregate bonds after being sprayed (dry) on the slope surface (Sunandar, 201). The soil aggregate bond is one of the factors that affect the soil resistance to erosion caused by rain water. Therefore, to answer these problems need to look for other adhesive materials that can bind aggregate soil to be better or stable. Latex is an alternative answer to the problem, however, the effect of latex on the growth of vegetation seeds in the hydroseeding mixture has not been studied. The purpose of this research paper is to compare the utilization of latex and polyacrilamide (PAM) in the mixture of hydroseeding to the growth of grass and cover crop vegetation. The research method used is RAK in time with 9 treatments, namely: PAM + grass seeds, latex + grass seeds bermuda, PAM + cover crop PJ, latex + cover crop seeds PJ, PAM + grass seeds rhodes, latex + grass seeds rhodes, PAM + grass seeds signal, latex + grass seeds signal and grass vetiver with 3 repetitions. The results showed an interaction between the combination of seeds and the soil amendment with time. In addition, this study shows that the use of Latex and PAM has no significant effect on growth. Therefore, hydroseeding technology using latex type feeding material is good enough to replace PAM Key Words: Hydroseeding, Lateks, Polyacrylamid (PAM), Rhodes, Signal, Bermuda, PJ